Macroergonomics for manufacturing systems : an evaluation approach /: an evaluation approach. ([2018]) - Realyvásquez-Vargas, Arturo; Maldonado-Macías, Aidé Aracely; García-Alcaraz, Jorge Luis
No abstract available